Deep-sea chitons from sunken wood in the West Pacific (Mollusca: Polyplacophora: Lepidopleurida): taxonomy, distribution, and seven new species - Sigwart, Julia D.; Sirenko, Boris I. (Zootaxa, 2012)
Natural deposits of sunken wood provide an important habitat for deep-sea invertebrates. Deep-sea chitons in the primitiveorder Lepidopleurida are typically collected rarely and as single specimens. However, these animals have been recoveredin large densities associated with sunken wood in the tropical West Pacific, in groups of up to 50 individuals. Four deep-sea expeditions in the West Pacific, to the Philippines, Solomon Islands, and Vanuatu, recovered a large number of poly-placophorans. We have examined the morphology as well as the range and distribution of these species, based on the larg-est collection ever examined (more than 1300 individuals). These species show potentially adapted characters associatedwith exploitation of sunken wood as habitat, such as protruding caps on sensory shell pores (aesthetes) and large interseg-mental bristles with potential sensory function. In this study we investigated the twenty-two species recovered, includingseven newly described here (Leptochiton consimilis n. sp., L. angustidens n. sp., L. dykei n. sp., L. samadiae n. sp., L.longisetosus n. sp., L. clarki n. sp., L. schwabei n. sp.), and provide the first identification key to the 34 lepidopleuran chitons known from sunken wood worldwide.